2018
DOI: 10.1039/c8sc00526e
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect hyperpolarisation of amines using parahydrogen

Abstract: Para-hydrogen achieves the hyperpolarisation of amines via SABRE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
95
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 57 publications
(99 citation statements)
references
References 72 publications
1
95
0
3
Order By: Relevance
“…Identification of the ligand trans to the hydride yielding the δ −27.6 resonance was secured by the nOe interactions to CH 3 groups of the imine and carbene. Kinetic product 4 major therefore is [Ir(H 2 )(amine)(IMes)(η 2 ‐ A )]Cl with the ligand arrangement shown in Scheme and logically arises due to the high lability of the amine when located trans to hydride ,. Similar α‐ ketoimine chelates with late transition metal centers have been reported for ruthenium, cobalt, nickel, copper and zinc .…”
Section: Methodsmentioning
confidence: 56%
See 1 more Smart Citation
“…Identification of the ligand trans to the hydride yielding the δ −27.6 resonance was secured by the nOe interactions to CH 3 groups of the imine and carbene. Kinetic product 4 major therefore is [Ir(H 2 )(amine)(IMes)(η 2 ‐ A )]Cl with the ligand arrangement shown in Scheme and logically arises due to the high lability of the amine when located trans to hydride ,. Similar α‐ ketoimine chelates with late transition metal centers have been reported for ruthenium, cobalt, nickel, copper and zinc .…”
Section: Methodsmentioning
confidence: 56%
“…These known products yield hydride resonances at δ−24.0 ( 2 ) and δ−23.7 ( 3 ) respectively . Furthermore, when these reactions are completed with p ‐H 2 , the free amine's NMR signals become strongly enhanced as a consequence of SABRE ,…”
Section: Methodsmentioning
confidence: 99%
“…For 1 Hn uclei, thermal polarization is only 1.02 10 À5 in a3T magnetic field, [4] and for other NMR-active spin-1/2 nuclei (e.g., 13 C, 15 N, 19 F, 31 P) with their lower gyromagnetic ratiosi ti se ven less. [6,[14][15][16][17][18] In some cases, the achieved enhancement was [a] Dr. The directu se of at hermally polarized signal of 15 Nn uclei for in vivo MRI applicationsi sv ery challenging because of the very low natural abundance of the 15 Ni sotope (0.365 %) and the lowerg yromagnetic ratio of 15 Nn uclei compared to 1 H ( % 1:10), resulting in low detection sensitivity.Asaresult, alimited number of 15 NM RI studies with non-isotopically enriched molecules were reported to date.…”
mentioning
confidence: 99%
“…[7][8][9][10][11] Parahydrogen servesa sasourceo fh yperpolarization in this method, and two SABRE approaches have been developed. [6,[14][15][16][17][18] In some cases, the achieved enhancement was [a] Dr. [12] In case of 15 Nn uclei, this process is most efficient at sub-microtesla magnetic fields (ca.…”
mentioning
confidence: 99%
See 1 more Smart Citation